Fabrication of micro cavities by micro electrical discharged machining - Ali, Mohammad Yeakub; Hung, Wayne N.P. (2000)
The LIGA (Lithography, Electroplating and Molding) technique can fabricate high aspect ratio micro components with sub-micrometer accuracy and few tens of nano meter surface finish. This technique uses deep x-ray lithography with synchrotron radiation and as a result, the process becomes very complex and expensive. Micro electrical discharged machining (Micro EDM) and focused ion beam (FIB) machining are identified as a cost-effective alternative for the fabrication of LIGA quality micro mold insert. This paper shows the preliminary results of the fabrication of micro mold insert for micro injection molding using nickel-beryllium alloy. Micro cavities are fabricated with micro EDM and investigated regarding aspect ratio, accuracy, surface finish, fabrication complexity, and cost. An aspect ratio of 5-6 and surface finish of 140 nano meter Ra are achieved. This machining process is found relatively simpler and faster compared to LIGA and other micro machining techniques such as lithography, dry or wet etching, FIB, etc. To be LIGA competitive, the micro mold insert produced by micro EDM should be further machined, such as with FIB, for higher accuracy and surface finish. The fabrication cost of a micro mold insert by this technique will be 20% of the cost when produced by the LIGA process.